Quantification of systemic renin-angiotensin system peptides of hypertensive black and white African men established from the RAS-Fingerprint®. (October 2016) - van Rooyen, JM; Poglitsch, M; Huisman, HW; Mels, CMC; Kruger, R; Malan, L; Botha, S; Lammertyn, L; Gafane, L; Schutte, AE
Objective: The objective of this study was to make use of a quantitative and qualitative approach comparing the systemic renin-angiotensin system (RAS) of hypertensive black and white African men by using RAS equilibrium analysis. Materials and methods: This sub-study involved 23 black ( n = 15) and white ( n = 8) hypertensive men aged 39.5–41 years, living in the North West Province of South Africa. The RAS-Fingerprinting was determined with LC-MS/MS quantification of angiotensin peptides. Blood pressure and other variables were determined with known methods. Results: The main finding of this study was the significant lower Ang I (<5.0 and 45.1 pg/ml; p = 0.005) and Ang II (15.6 and 123.9 pg/ml; p ⩽ 0.001) encountered in the hypertensive black African men compared to their white counterparts. Levels of Ang 1-5 (downstream metabolite of Ang 1-7) (1.8 and 3.0 pg/ml), were detected in black and white hypertensive men, respectively. Conclusions: The observed differences between circulating RAS components, which are reflected via equilibrium angiotensin levels, point to a distinctive molecular regulation of the RAAS in the two study cohorts. The increased peripheral resistance observed in hypertensive black individuals might take over a dominant role in control of blood pressure in this study population. A novel highly sensitive LC-MS/MS method resolved the issue of peptide recovery variations during sample preparation by using internal standards for each individual angiotensin metabolite.